Predicting the equity premium via its components - Fabian Bätje; Lukas Menkhoff (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We propose a refined way of forecasting the equity premium. Our approach rests on the sum-of-parts approach which disaggregates the equity premium into four components. Each of these components is predicted separately, following the approach of Ferreira and Santa-Clara (2011). We extend the set of standard macroeconomic variables by also using technical indicators as predictors. We find that macro indicators best predict the price-earnings multiple, whereas technical indicators better predict earnings growth. Applying this allocation generates superior forecast performance, statistically and economically. Moreover, we show that macroeconomic and technical indicators inform about complementary aspects of the business cycle.
Keywords: G17; G11; C53; 330